Cellular Senescence as the Pathogenic Hub of Diabetes-Related Wound Chronicity - Berlanga-Acosta, Jorge A.; Guillén-Nieto, Gerardo E.; Rodríguez-Rodríguez, Nadia; Mendoza-Mari, Yssel; Bringas-Vega, Maria Luisa; Berlanga-Saez, Jorge O.; García del Barco Herrera, Diana; Martinez-Jimenez, Indira; Hernandez-Gutierrez, Sandra; Valdés-Sosa, Pedro A. (Frontiers in Endocrinology, 2020)
Diabetes is constantly increasing at a rate that outpaces genetic variation and approaches to pandemic magnitude. Skin cells physiology and the cutaneous healing response are progressively undermined in diabetes which predisposes to lower limb ulceration, recidivism, and subsequent lower extremities amputation as a frightened complication. The molecular operators whereby diabetes reduces tissues resilience and hampers the repair mechanisms remain elusive. We have accrued the notion that diabetic environment embraces preconditioning factors that definitively propel premature cellular senescence, and that ulcer cells senescence impair the healing response. Hyperglycemia/oxidative stress/mitochondrial and DNA damage may act as major drivers sculpturing the senescent phenotype. We review here historical and recent evidences that substantiate the hypothesis that diabetic foot ulcers healing trajectory, is definitively impinged by a self-expanding and self-perpetuative senescent cells society that drives wound chronicity. This society may be fostered by a diabetic archetypal secretome that induces replicative senescence in dermal fibroblasts, endothelial cells, and keratinocytes. Mesenchymal stem cells are also susceptible to major diabetic senescence drivers, which accounts for the inability of these cells to appropriately assist in diabetics wound healing. Thus, the use of autologous stem cells has not translated in significant clinical outcomes. Novel and multifaceted therapeutic approaches are required to pharmacologically mitigate the diabetic cellular senescence operators and reduce the secondary multi-organs complications. The senescent cells society and its adjunctive secretome could be an ideal local target to manipulate diabetic ulcers and prevent wound chronification and acute recidivism. This futuristic goal demands harnessing the diabetic wound chronicity epigenomic signature.